Indigenous Knowledge in The Framework of Ethnopedagogy for Merdeka Curriculum in Elementary Schools - Gandasari, Adriana; Hernawan, Asep Herry; Wahyudin, Dinn; Supiandi, Markus Iyus; Aristo, Thomas Joni Verawanto; Oktaviani, Ursula Dwi; Janius, Leonardo; Mawardi, Mawardi; Trianni, Thenni Debby; Bungkas, Magdalena Victoria (International Conference on Elementary Education, 2025)
The Indonesian nation as a great nation has extraordinary wealth, one of which is indigenous knowledge spread from Sabang to Merauke. Preventive action is needed so that indigenous knowledge can be preserved so that it does not become extinct, one of which is through education in the form of ethnopedagogy. The research was conducted to find the potential and inventorying the indigenous knowledge of the Dayak, Malay, and Chinese communities of Sintang Regency, West Kalimantan, Indonesia in the form of ethnopedagogy. The research uses a descriptive qualitative approach with an exploratory survey approach to informants consisting of primary informants, key informants, and recommendations informants through in-depth interviews. The results study show that 12 indigenous knowledge can be implemented in the Merdeka Curriculum in the form of ethnopedagogy for elementary schools. The results of this study provide a recommendation on indigenous knowledge in the ethnopedagogical framework for elementary schools that can be applied in elementary schools in Sintang Regency, West Kalimantan.